A CROSS-JURISDICTIONAL COMPARISON OF MSME INSOLVENCY FRAMEWORKS IN INDONESIA AND SINGAPORE - Recca Ayu Hapsari; Tata Wijayanta; Irna Nurhayati; Stanislav Vladimirov Mladenov (Faculty of Law, Universitas Lampung, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are central to Indonesia’s economy but remain highly vulnerable during financial crises, partly due to the absence of a dedicated insolvency regime under Law No. 37 of 2004. This study identifies structural gaps in Indonesia’s bankruptcy framework, particularly its misalignment with MSME characteristics under Law No. 20 of 2008, including unclear legal subject status and weak asset separation that expose owners’ personal assets to bankruptcy risks. Using a socio-legal approach that combines statutory analysis, court decisions, interviews with MSME stakeholders, and bankruptcy data from Indonesia and Singapore, the study finds that Indonesian MSMEs face slow procedures, high costs, limited institutional support, and low awareness of insolvency remedies, leading to underutilization of existing mechanisms. In contrast, Singapore’s simplified insolvency framework demonstrates how tailored, low-cost procedures can support MSME recovery and sustainability. The study argues for reforming Indonesia’s bankruptcy law to improve accessibility, efficiency, and legal certainty for MSMEs, thereby strengthening entrepreneurship and long-term economic stability.